Supply Chain Management: A Logistics Perspective, 11th Edition - C. Langley (Cengage Learning, 2020)
Using a reader-friendly style and straightforward, interesting approach, SUPPLY CHAIN MANAGEMENT: A LOGISTICS PERSPECTIVE, 11E blends logistics theory with practical applications. The latest content highlights emerging issues, technology developments, and global changes in the constantly evolving field of supply chain management today. This digital edition examines today's real companies and how public and private organizations are responding to the continual pressure to modernize and transform their supply chains. Updated features and short cases offer hands-on managerial experience as you examine the key decisions and circumstances that supply chain managers face daily. New profiles introduce each chapter with real organizations, people, or events that emphasize the relevance of what you are learning. Technology-focused features and global content examine key areas where change is occurring and provide a meaningful perspective on how today's changes impact current and future supply chains.